SURAT WASIAT SEBAGAI PENGHINDAR CAMPURTANGAN PEMERINTAH DI AMERIKA SERIKAT BAGAIAN SELATAN - Tatit Hariyanti (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Southerners are famous for their exaltation of their honor and the sanctity of their private property. Any obstacles in the ownership and the management of their private property will be regarded as a form of interference and will be eliminated or at least minimalized. Intestacy laws and death taxes are regarded as the government’ s interference. Intestacy laws are applied when there is no valid last will and testament. The taxes will be high or low depending of the smartness in utilizing the offered deduction through last will and testament. Key words: sanctity of private property, honor, intestacy laws, taxes, interference, last will and testament.